2007
DOI: 10.1128/iai.00762-07
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Play an Important Role in Host Resistance to Respiratory Infection with Acinetobacter baumannii in Mice

Abstract: Acinetobacter baumannii has emerged as a major cause of both community-associated and nosocomial pneumonia, but little is known about the cellular and molecular mechanisms of host defense against respiratory infection with this bacterial pathogen. In this study, we examined the role of neutrophils in host resistance to pulmonary A. baumannii infection in a mouse model of intranasal (i.n.) infection. We found that neutrophils were rapidly recruited to the lungs following i.n. inoculation of the pathogen and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
250
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(265 citation statements)
references
References 34 publications
13
250
2
Order By: Relevance
“…15,16) Treatment of mice with anti-IFN-monoclonal antibody resulted in delayed clearance of Bordetella pertussis in the respiratory tract. 17) In our study, the olive oil-fed mice subjected to isolation stress showed a temporarily delayed clearance of the fungus in the liver at day 3 after infection (Table 3) and greater liver IFN-production at day 8 (Table 4) than the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) Treatment of mice with anti-IFN-monoclonal antibody resulted in delayed clearance of Bordetella pertussis in the respiratory tract. 17) In our study, the olive oil-fed mice subjected to isolation stress showed a temporarily delayed clearance of the fungus in the liver at day 3 after infection (Table 3) and greater liver IFN-production at day 8 (Table 4) than the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…This specific response includes the release of pro-inflammatory cytokines and chemokines (8,15,16). IL-6, TNF-α, and IL-1ÎČ are representative proinflammatory cytokines and are associated with the upregulation of cell adhesion molecules and antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the overall low virulence of most A. baumannii strains in rodent models of infection, investigators have used various methods to enhance virulence, including mixing bacterial inocula with porcine mucin (49,60) or the use of neutropenic mouse models of A. baumannii infections (36,67,75). However, neutropenia is a rare clinical risk factor for patients with A. baumannii infections (1a, 6, 7, 20, 26, 34, 40, 50), and therefore an alternative model of A. baumannii infection in immunocompetent animals is desirable to more accurately mimic the types of infections caused by this organism.…”
Section: Discussionmentioning
confidence: 99%